Geographic differentiation in adaptive traits of wild chestnut Spanish populations (Castanea sativa Miller) - Fernandez-Lopez, J.; Zas, R.; Blanco-Silva, R.; Díaz, R. (Forest Systems, 2005)
Flushing, spring frost damages and height were recorded in a provenance test including nineteen populations covering most Spanish chestnut distribution and were analysed to study the differentiation among wild populations. There was remarkable differentiation among populations in flushing time and height growth and Qst was higher for flushing and frost damage, and lower for height. The coefficients of quantitative differentiation among populations were similar to the values obtained for other autochthonous species. Spanish chestnut wild populations were classified in three groups: early flushing xeric populations from the Mediterranean, late flushing populations from northern mountains and intermediate flushing populations from Galician coast and Canary Islands. The observation of variability patterns indicated the importance of natural selection and a restricted gene flow as factors shaping the structure of wild populations in Spain. The use of local sources in plantations was recommended.